Excitonic Transition Energy Renormalization in Lead Diiodide Nanofilm Caused by Self-Polarization Effects and Electron-Phonon Interaction - O.V. Pugantseva; V.M. Kramar (Журнал нано- та електронної фізики)
Results of the theoretical study of the contributions of self-polarization effect and exciton-phonon interaction to the exciton transition energy in a flat semiconductor nanofilm are presented here. Calculations of the binding and exciton ground state energies are performed using 2H-PbI2 nanofilm embedded in ethylene-methacrylic acid (E-MAA) copolymer. It has been revealed that in ultrathin nanofilms the self-pola-rization effect contribution to the exciton energy is more than from the interaction with polarizing optical phonons.